EFEKTIVITAS PEMBELAJARAN BERBASIS MASALAH DALAM MENINGKATKAN KEMAMPUAN MENULIS NARASI MATA PELAJARAN BHS.INDONESIA DI KELAS X SMKN 2 GOWA - Naimi; Sri Fitrah Lestari; Nasmiati Nasaruddin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This study aims to assess the effectiveness of implementing problem-based learning in improving the narrative writing skills of tenth-grade students at SMKN 2 Gowa. The focus of the research is the low narrative writing ability among students. The method used in this study is a classroom action research (CAR) approach, designed in two cycles. Each cycle consists of planning, implementation, observation, and reflection stages. The subjects of this study involved 20 randomly selected tenth-grade students to ensure representativeness. Data were collected through narrative writing skill tests and direct observations during the learning process. The results of the data analysis indicate a significant improvement in the students' narrative writing skills. The average score obtained by students before the implementation of the problem-based learning model was 60, which increased to 78 by the end of the first cycle, and reached 85 by the end of the second cycle. This improvement in scores shows that students became more active and engaged in the learning activities. Additionally, observation results noted an increase in motivation among students during the learning process. Therefore, it can be concluded that problem-based learning is effective in improving the narrative writing skills of tenth-grade students at SMKN 2 Gowa and can serve as an innovative and engaging teaching model alternative.